Quenching and heat treatment of welded duplex stainless steel to avoid intergranular corrosion - Dan, N.E. (Asian Research Publishing Network, 2016)
Stainless steel has been known for its high performance in manufacturing industries, oil and gas industries for minimum susceptibility to defect such as corrosion. Welding is a relevant joining process with heat application capable of altering the microstructure of corrosion resistance alloy CRA. Intergranular corrosion or weld decay is a welding defect in stainless steel due to sensitization known as the formation of chromium carbide on heat affected zone. Analysis of quenched sample in water, normalized sample after welding and heat treatment sample after welding were studied using SEM, hardness test and energy dispersive spectroscopy. The result obtained from SEM showed that there was more carbide precipitation on welded sample without quenching and heat treatment. EDS suggested that less composition of chromium at heat affected region of quench and heat treated sample. Â© 2006-2016 Asian Research Publishing Network (ARPN).